2003
DOI: 10.1002/psc.458
|View full text |Cite
|
Sign up to set email alerts
|

Efficient protocols for the synthesis of enantiopure γ‐amino acids with proteinogenic side chains

Abstract: The synthesis of enantiopure gamma-substituted gamma-amino acids with proteinogenic side chains, starting from the corresponding natural alpha-amino acids, was studied. N-Protected amino aldehydes containing various protective groups were prepared from the corresponding amino alcohols by oxidation with NaOCl in the presence of AcNH-TEMPO and directly reacted with methyl, benzyl and tert-butyl phosphoranylidene acetate to produce alpha,beta-unsaturated gamma-amino esters. Simultaneous hydrogenation of the doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…4,5 The derivatives of γ-amino buryric acid (GABA) could be potential, selective and irreversible inhibitors of GABA amino transferase, the enzyme involved in the catabolism of GABA. 6,7 As in principle γ-lactams should be easily obtained from the corresponding γ-N-hydroxylamino esters we have paid our attention to the synthesis of biologically important γ-amino acids from the sugar-derived nitrones previously used by us in the chiral cycloadditions. In this communication we wish to describe the SmI 2 -induced coupling of N-benzylsubstituted D-xylose and D-lyxose derived nitrones with methyl acrylate under the formation of chiral 4-substituted γ-N-hydroxylamino esters.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 The derivatives of γ-amino buryric acid (GABA) could be potential, selective and irreversible inhibitors of GABA amino transferase, the enzyme involved in the catabolism of GABA. 6,7 As in principle γ-lactams should be easily obtained from the corresponding γ-N-hydroxylamino esters we have paid our attention to the synthesis of biologically important γ-amino acids from the sugar-derived nitrones previously used by us in the chiral cycloadditions. In this communication we wish to describe the SmI 2 -induced coupling of N-benzylsubstituted D-xylose and D-lyxose derived nitrones with methyl acrylate under the formation of chiral 4-substituted γ-N-hydroxylamino esters.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, catalytic hydrogenation of 307 followed by treatment with trifluoroacetic acid produced N-Fmoc-c-amino acid 309a in 58% yield (Scheme 71). 127 More recently, Tamamura et al 128 reported the synthesis of N-Fmoc-c-amino acid 309b under a similar protocol. Thus, the reduction of amide 310 obtained from L L-b-(2-naphthyl)alanine, with DIBAL-H, followed by HornerWadsworth-Emmons reaction afforded the N-Boc-c-amino acid tert-butyl ester 311 in 78% yield, which by catalytic hydrogenation gave compound 312 in 74% yield.…”
Section: C-substituted C-amino Acidsmentioning
confidence: 98%
“…The key step is a Michael addition of the lithium anion of diethyldifluoromethanephosphonate to a p-chloro-b-nitro styrene (112). Reduction of the nitro functionality and ester hydrolysis of (113) affords the desired phosphonic amino acids (114).…”
Section: Baclofen and Analogsmentioning
confidence: 99%
“…Alternatively, a Wittig reaction with an alkyl (triphenylphosphoranylidene)acetate on a-amino aldehydes such as phenylalaninal (115) and subsequent reduction of the resulting alkene (116) has been employed (Scheme 14.33). Hydrolysis of the protecting group affords the g-substituted g-amino acid (117) [112].…”
Section: Baclofen and Analogsmentioning
confidence: 99%